Polymer nanocomposite membranes for reverse osmosis - Anthonette, James; Md. Rezaur, Rahman; Norazzlina, M.Sa'don; Muhammad Khusairy, Bakri; Ain Zaienah, Sueraya (Elsevier Ltd., 2025)
As the world continues to develop, industrialization and population growth are inevitable outcomes. The rapid escalation of global development has presented a dual narrative: one of advancement and progress, and the other showcasing adverse impacts on the environment (Pandey & Asif, 2022). Amidst this complex interplay, water bodies stand out as critical arenas of concern due to the consequences of anthropogenic impacts. The human-induced pressures, including overexploitation of natural resources, pollution, and habitat degradation, have led to a multitude of challenges to biodiversity with significant implications for global climate change (Sponsel, 2024). Additionally, the continuous discharge of wastewater containing pesticides, herbicides, dyes, heavy metals, pharmaceuticals, and organic residues has emerged as a major contributor to water quality degradation, a prominent concern within environmental circles (Hejna et al., 2022; Li et al., 2022; Mitra et al., 2022; Rahman et al., 2021; Saleh et al., 2020; Wen et al., 2017). This issue severely threatens human life due to the depletion of clean water and scarcity. According to the United Nations, more than two billion people live in countries experiencing high water stress, and by 2025 nearly two thirds of the global population could suffer from water shortages (Boretti, 2022). Climate change is exacerbating this crisis, which is causing changes in weather patterns and water distribution. Vulnerable communities, especially in developing countries, are disproportionately affected where clean and life saving water is essential for survival (Tzanakakis et al., 2020). This crisis needs an all encompassing strategy to deal with it by elevating ventures in both water efficient technologies and wastewater treatment systems (Abdul Rahman et al., 2023). Besides, the value of integrated water resource management, which takes system wide dimensions of water uses and impacts into account, cannot be overstated (Dolan et al., 2021). It recognizes the transboundary and intersectoral nature of water systems and urges cooperation among different organizations to address this challenge.